Enhancing the Quality of Ready-to-Drink Robusta Coffee through Enzymatic Decaffeination, Cold Brew Techniques, and Sterilization - Rahma Widya Puspita; Chusnul Hidayat; Supriyadi Supriyadi (agriTECH, 2026)
Cold brew coffee has been reported to possess distinct sensory characteristics compared to hot brew. Therefore, this study aims to enhance the flavor of decaffeinated robusta cold brew coffee as a specialty coffee. The decaffeination process (using bromelain enzyme from pineapple), cold brew (immersion method), and sterilization techniques were used to examine the sensory qualities and physicochemical characteristics (color, pH, TDS, caffeine, chlorogenic acid/CGA, trigonelline, and volatile compounds) of decaffeinated robusta cold brew coffee and ready-to-drink decaffeinated robusta cold brew coffee. Medium-roasted robusta coffee was used in 2 different brewing methods, namely cold brew (T= 15 °C, 20 °C, 25 °C; t= 8, 10, 12 h) and hot brew as a control. The sensory analysis was conducted by trained panelists from Indonesian Coffee and Cocoa Research Institute using cupping technique. The Specialty Coffee American Association (SCAA) method was used to determine the flavor profile of a fine robusta cupping form.The results showed that the highest overall sensory score was obtained by decaffeinated cold brew robusta at 20°C for 8 hours. It contained 0.081 mg/100 g caffeine, 0.024 mg/100 g CGA, and 0.048 mg/100 g trigonellineSpecialty coffee could be defined as ready-to-drink cold brew coffee brewed at 20 °C for 10 hours, 25 °C for 8 hours, and 25 °C for 10 hours. Notes, such as brown sugar, honey, caramel, chocolate, and herbal, were enhanced by sterilization, while hot brew coffee presented a less favorable profile, scoring only 78.25.